(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Diesel oil has been the preferred base fluid for the formulation of oil-based drilling mud. Diesel oil has negative effects on the environment and there is a growing need for more environmentally sustainable alternatives that can be technically compared to diesel base oil. In recent times, the use of vegetable oils as drilling fluid base oil has been of interest. In this study, 1378 kg/m3 of palm kernel oil-base mud (PKOBM) and palm kernel oil biodiesel base mud (BDBM) were experimentally formulated. The BDBM was synthesized by the transesterification of vegetable (palm kernel) oil. The performance of PKOBM and BDBM was then evaluated against conventional diesel oil-base mud (DOBM). The evaluation performed was based on the rheological, filtration and wall building properties, emulsion and thermal stabilities, and acute toxicity of the formulated drilling fluid systems.Results obtained from the study reveal that the mud systems (PKOBM and BDBM) show a typical Herschel-Bulkley (modified power-law) drilling mud rheological pattern at temperatures of 49 oC, 66 oC and 80 oC. BDBM showed comparable rheological properties with better hole cleaning capacity as indicated by a lower flow index. For the filtrate loss test, BDBM exhibited slightly lower filtrate loss of 3.2 ml compared to DOBM with 3.2 ml, whereas PKOBM had a higher fluid loss of 4.4 ml. For the filter cake and thermal stability test, there were no significant changes between DOBM and BDBM whereas PKOBM had the least desirable performance. BDBM exhibited the most stable emulsion of 1274 volts breaking voltage and PKOBM, least with 739 volts compared to 1169 volts breaking voltage of DOBM. This study concludes that BDBM could be used as an environmentally sustainable substitute for diesel oil-based mud (DOBM).